Postage Stamp Precision Technique of Dorsal Hump Reduction - Bhat, Uday; Peswani, Amit; Katyal, Ishita; T.C, Anudeep; Pawar, Mangesh; P.N, Suparna; Goel, Richa (Indian Journal of Plastic Surgery, 2025)
Background The conventional methods of dorsal hump reduction planning and execution are prone to errors. The amount to be lowered is usually subject to surgeon's judgment and errors are possible due to differential skin thickness of envelope.Objectives We propose a hump reduction technique that includes a method to precisely plan the amount of excision based on real surface measurements and our postage stamp technique of hump reduction.Materials and Methods A prospective study was done in 25 patients requiring dorsal hump reduction. The planning of hump reduction includes precisely plotting the extent of the hump from fixed landmarks on the skin and recreating these distances on the framework after raising the envelope. In contrast to the traditional continuous bony cut in caudocranial direction, we used serial perforations along the proposed profile line. These postage stamp cuts are made using 2 mm osteotome and are converted into a continuous cut using the double-guarded osteotome.Results All 20 patients were followed till 1 year. There was no major complication and all patients were satisfied with the appearance.Conclusion Our technique negates the errors in planning and execution. It also helps in reducing the learning curve associated with the control of osteotome making it beneficial for a novice plastic surgeon. It is particularly useful for small humps, and can be used both in open and closed rhinoplasty making it a very good alternative to conventional hump reduction techniques.
Keywords: rhinoplasty; hump reduction; dorsal Hump